Developing an English Course Teaching Plan for a Semester from the Task-Based Language Teaching (TBLT) for the Mathematics Department Students at Zainul Hasan Islamic University of Probolinggo - Zainuddin; Hamdani, Beny (Institut Agama Islam Negeri Ponorogo, 2024)
The development of a Teaching Plan for a Semester (TPS) is directly related to the analysis of competency standards, teaching methods, and learning evaluation. Based on that, the specific targets to be achieved in this research include two things. The two objectives are (i) to formulate graduates' English learning outcomes based on needs analysis and objective analysis of input English proficiency and (ii) to design learning materials to meet the formulated learning outcomes. In general, the research method used is the development research method of Gall, Borg, Van den Akker, Gravemeijer, McKenney, and Nieven. Meanwhile, the approach used in this study is a combination of the ADDIE approach from Branch and the systems approach from Dick and Carey. The results of the study show that the level of English language needs indicated by stakeholders must be adapted. This adaptation is based on input competencies that do not meet the standards to be put into the ESP stage purely. Therefore, the design of the ESP lesson plan is still carried out by considering matters related to the input of general English competence.